The Economics of Corporate Trade Credit in Europe (Taylor & Francis, 2021)
This book is a research monograph addressed to a wide range of academics interested in corporate short-term capital. The study shows the role of trade credit in the functioning of economic entities. It constitutes a comprehensive source of knowledge about the role of trade credit in the development of enterprises, as well as the impact of this form of finance on the development of economies. Apart from an extensive review of the theoretical aspects of the role of trade credit in the economy, the study discusses the importance of factors influencing trade credit behaviour. Trade credit, despite its versatility, has not yet been fully described, particularly with regard to the specificity of domestic markets. This study aggregates and supplements the existing sources. The monograph is of an international character, as it covers a substantial group of European countries. Therefore, it is likely to have international appeal. The findings may be of interest to those involved in finance management. Understanding the differences in receivables management resulting from the country specificity can contribute to a better understanding of business finance and its operational functions. This knowledge may support the effective management of receivables and liabilities, especially in companies operating on the global market.
English
Keywords: Accounting; Corporate finance; Economics; cluster analysis; country and firm size effect;financial crisis; industry; payables management; receivables management; short-term finance;Trade credit; trade credit balance; working capital